Use of thyroid hormone in hypothyroid patients and euthyroid subjects in Spain: A THESIS questionnaire survey - Galofré, Juan C; Attanasio, Roberto; Hegedüs, Laszlo; Nagy, Endre; Negro, Roberto; Papini, Enrico; Perros, Petros; Díez, Juan J (Endocrinología, diabetes y nutrición., 2022)
Hypothyroidism is one of the leading conditions in endocrinology. Despite that fact, clinical indications for treatment still vary among Spanish specialists. To identify attitudes of Spanish specialists relating to the use of levothyroxine (LT4) and the management of hypothyroidism. The members of the Sociedad Española de Endocrinología y Nutrición (Spanish Society of Endocrinology and Nutrition) were invited to participate in a web-based survey. The survey, initially in English, was modified to reflect in accordance with the availability of thyroid hormone formulations in Spain. A total of 505 of 1956 (25.8%) members (66% female) completed the survey; 97.4% declared that LT4 is the first-line therapy for hypothyroidism. The indications for LT4 therapy in euthyroidism were infertility in thyroid antibody-positive women (48.5%) and simple goitre (21.2%). However, 44.2% of specialists reported that there was no indication for LT4 therapy in such patients. Only a minority of respondents (2.6%) considered combining LT4 with liothyronine as the treatment of choice from inception, whereas 49% stated that it should never be used. The standard of treatment of hypothyroidism in Spain is almost exclusively with LT4 tablets. Availability of other formulations of LT4 or combination therapy for hypothyroidism management remains to be explored, especially in patients with persistent symptoms. Notably, non-evidence-based use of LT4 is widely practiced in Spain for euthyroid women with autoimmune thyroiditis and fertility issues.